적응형 문턱치와 QRS피크 변화에 따른 P파 검출 알고리즘 - 조익성(Ik-sung Cho); 김주만(Joo-Man Kim); 이완직(Wan-Jik Lee); 권혁숭(Hyeog-soong Kwon) (한국정보통신학회논문지, 2016)
P wave is cardiac parameters that represent the electrical and physiological characteristics, it is very important to diagnose atrial arrhythmia. However, It is very difficult to detect because of the small size compared to R wave and the various morphology. Several methods for detecting P wave has been proposed, such as frequency analysis and non-linear approach. However, in the case of conduction abnormality such as AV block or atrial arrhythmia, detection accuracy is at the lower level. We propose P wave detection algorithm through adaptive threshold and QRS peak variability. For this purpose, we detected Q, R, S wave from noise-free ECG signal through the preprocessing method. And then we classified three pattern of P wave by peak variability and detected adaptive window and threshold. The performance of P wave detection is evaluated by using 48 record of MIT-BIH arrhythmia database. The achieved scores indicate the average detection rate of 92.60%. P파는 심장의 전기적, 생리적 특성을 나타내는 파라미터로써 심방성 부정맥 진단에 있어 매우 중요하다. 하지만 R파에 비해 신호의 크기가 작고 그 형태가 다양하여 검출에 많은 어려움이 있다. P 파를 검출하기 위한 기존 연구방법으로는 주파수 분석과 비선형 접근방법 등이 제안되어 왔지만 방실 차단과 같은 전도 이상이나 심방성 부정맥의 경우에는 검출 정확도가 낮아진다. 이는 심장 상태에 따라 다양한 모양의 P파의 패턴이 존재하기 때문이다. 본 연구에서는 QRS 피크 변화에 따른 P파의 패턴을 분류하고 적응형 문턱치를 이용하여 P파를 검출하는 방법을 제안한다. 이를 위해 전처리를 통해 잡음이 제거된 심전도 신호에서 Q, R, S를 검출한다. 이후 피크 변화에 따른 P파의 3가지 패턴을 분류하고 적응형 윈도우와 문턱치를 통해 P파를 검출하였다. 제안한 방법의 우수성을 입증하기 위해 MIT-BIH 부정맥 데이터베이스 48개의 레코드를 대상으로 한 P파의 평균 검출율은 92.60%의 성능을 나타내었다.